MATRIKS INVERS MOORE-PENROSE DALAM PENYELESAIAN SISTEM PERSAMAAN LINIER - R., IDA M.; Udjiani, Titi (MATEMATIKA, 2009)
In this paper we define and study about The Moore Penrose Inverse of any matrices under the rank. We apply our result to study of Solution Linear Equation Sistem Â